ANALISA PENGARUH TRANSACTION COST TERHADAP LAMANYA HOLDING PERIOD SAHAM BIASA: - LENNY LENNY; NUR. INDRIANTORO (Jurnal Bisnis dan Akuntansi, 1999)
The objective of the study is to test the relationship between transaction cost and holding periods for common stocks. Transaction costs in this study refer to the variable cost of bid ask spreads, the cost that varies across securities and also cause the clientele effect. The clientele effect affects the frequency with which investors trade securities and causes investors with longer (shorter) expected holding periods to hold the assets with the higher (lower) transaction costs. This study investigates whether investors with longer (shorter) investment time horizons hold common stocks with higher (lower) bid - ask spreads. The statistical method used in this study is two - stage least squares regression, then T - test, regression coefficient, and F - test on the 5% level of significance. Sample is taken from the population of all stock listed in Jakarta Stock Exchange from 1995 through 1996 period. There are 45 chosen stock for the index of LiQuid which should be the highest in market capitalization and liquidation. The statistical results show that bid - ask spreads relate positively but insignificantly of the holding periods for the T - test . Nevertheless, the F - test is significant, which means that bid - ask spreads, market value, and variance return can be used for predicting the variations of holding period.